The War of 1812 conflict for a continent - Stagg, J. C. A. (Cambridge essential histories, 2012)
A short and easily-readable book that will explain to both Americans and Canadians why the War of 1812 mattered in the histories of their two nations. Its contents provide far more that merely the military history of the failed American campaigns against Canada between 1812 and 1815.